2017
DOI: 10.1155/2017/4097195
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Studies on Quercus acuta Thunb. (Fagaceae) Extract: Active Constituents, Serum Uric Acid Suppression, and Xanthine Oxidase Inhibitory Activity

Abstract: Quercus acuta Thunb. (Fagaceae) (QA) is cultivated as a dietary and ornamental plant in China, Japan, South Korea, and Taiwan. It has been widely used as the main ingredient of acorn tofu, a traditional food in China and South Korea. The aim of this study was to determine in vitro and in vivo xanthine oxidase (XO) inhibitory and antihyperuricemic activities of an ethyl acetate extract of QA leaf (QALE) and identify its active phytochemicals using gas chromatography-mass spectrometry (GC-MS) and liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The XO inhibitory activity of the 80% ethanolic extract tended to increase in a concentration-dependent manner with increasing the extract concentration tested by up to 2 mg/mL (data not shown). Previously, we reported four different botanical extracts as potential XO inhibitors [ 18 ]. Yoon et al [ 19 , 20 ] reported that the optimized extracts of Corylopsis coreana and Camellia japonica inhibited XO activity by approximately 50% at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XO inhibitory activity of the 80% ethanolic extract tended to increase in a concentration-dependent manner with increasing the extract concentration tested by up to 2 mg/mL (data not shown). Previously, we reported four different botanical extracts as potential XO inhibitors [ 18 ]. Yoon et al [ 19 , 20 ] reported that the optimized extracts of Corylopsis coreana and Camellia japonica inhibited XO activity by approximately 50% at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Yoon et al [ 19 , 20 ] reported that the optimized extracts of Corylopsis coreana and Camellia japonica inhibited XO activity by approximately 50% at a concentration of 2 mg/mL. Additionally, Yoon et al [ 18 ] demonstrated that Quercus acuta extract showed approximately 50% XO inhibitory activity at a concentration of 1 mg/mL. Cudrania tricuspidata extract inhibited XO by approximately 75% at a concentration of 2 mg/mL [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we had screened various medicinal sources for XO inhibitory activity. Among 229 medicinal plant extracts, 3 extracts were selected as potential XO inhibitors [ 26 ]. Extracts from Corylopsis coreana and Camellia japonica inhibited the XO at a concentration of 2 mg/mL, and relative inhibiton levels were 50% to 60% [ 20 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extracts from Corylopsis coreana and Camellia japonica inhibited the XO at a concentration of 2 mg/mL, and relative inhibiton levels were 50% to 60% [ 20 , 27 ]. The extract from Quercus acuta inhibited the XO at a concentration of 1 mg/mL, and the inhibition level was ~50% [ 26 ]. The plant extracts with XO inhibitory activity in the range of 1–2 mg/mL demonstrated consistent effects in the in vivo animal disease model.…”
Section: Resultsmentioning
confidence: 99%
“…Quercus acuta (QA) is widely distributed in the southern part of Korea, China, Japan, and Taiwan [ 1 ]. It is mainly cultivated as an ornamental plant in Japan, and its fruit (acorn) is the main ingredient in acorn jelly, which is a popular traditional food in Korea [ 2 ].…”
Section: Introductionmentioning
confidence: 99%